Pengaruh Pengetahuan Investasi dan Motivasi Investasi Terhadap Minat Berinvestasi Di Pasar Modal Syariah Pada Mahasiswa Prodi Ekonomi Syariah IAIN Sorong - Bambang Sunatar; Muhammad Hendra; Suharmoko Suharmoko (Program Studi Manajemen Universitas Muslim Maros, 2023)
The purpose of this study was to examine the effect of investment knowledge and investment motivation on interest in investing in the Islamic capital market for students of Islamic economics study program IAIN Sorong. The research method used is a quantitative research method with descriptive analysis and multiple linear regression analysis models. The population in this study were students of Islamic economics study program IAIN Sorong totaling 372 people. The sample technique used is purposive sampling technique with an error rate of 5% so that the sample used is 100 people. The results of this study indicate that investment knowledge has a positive and significant effect on interest in investing in the Islamic capital market as evidenced by the value of t count > t table (6,832 > 1,984) and a significance value of 0.000 < 0.05. so it can be concluded that H1 is. Accepted Investment motivation has a positive and significant effect on interest in investing in the Islamic capital market as evidenced by the value of t count > t table (14,041 > 1,984) and a significant value of 0.000 < 0.05. so it can be concluded that H2 is. acceptedThen investment knowledge and investment motivation have a simultaneous effect on interest in investing in the Islamic capital market as evidenced by the f test results obtained by f arithmetic > f table (98,847 > 3.09). so it can be concluded that H3 is accepted. Investment knowledge; Investment motivation; Investment interest; Islamic Capital Market